Integrating Ethnomathematics into Guided Inquiry Learning: Designing Culturally Responsive Mathematics Instruction to Support Students’ Mathematical Reasoning, Connections, and Appreciation - Dhoriva Urwatul Wutsqa; Hery Nugroho; Septi Yana Wulandari (Universitas Papua, 2026)
Although numerous studies have developed guided inquiry-based instructional materials for mathematics education, most have relied on generic problem contexts and have given limited attention to the integration of ethnomathematics as a meaningful cultural resource for learning. Furthermore, prior research has focused primarily on cognitive outcomes, leaving the combined influence of inquiry-based instruction on students’ mathematical reasoning, mathematical connections, and mathematical appreciation underexplored. To address this gap, this study aimed to describe the design process and evaluate the implementation of Ethnomathematics-Integrated Guided Inquiry Teaching Devices (GITD-E). Employing a Research and Development (R&D) approach based on the ADDIE framework, the study involved Grade VII students at a junior high school in Yogyakarta, Indonesia. Data were collected through expert validation, practicality questionnaires, classroom observations, and post-test assessments, while implementation outcomes were examined using a one-shot case study design. The findings indicate that the developed GITD-E met established criteria of validity and practicality and yielded positive learning outcomes. In addition, integrating local cultural contexts appeared to enhance students’ engagement and support more meaningful mathematics learning experiences. Theoretically, this study extends guided inquiry learning by positioning ethnomathematics as a contextual dimension within inquiry-based mathematics instruction. Practically, it offers insights for designing culturally responsive, contextually relevant, and student-centered mathematics learning environments.